2009
DOI: 10.1007/s10822-009-9286-z
|View full text |Cite
|
Sign up to set email alerts
|

Computational fragment-based drug design to explore the hydrophobic sub-pocket of the mitotic kinesin Eg5 allosteric binding site

Abstract: Eg5, a mitotic kinesin exclusively involved in the formation and function of the mitotic spindle has attracted interest as an anticancer drug target. Eg5 is co-crystallized with several inhibitors bound to its allosteric binding pocket. Each of these occupies a pocket formed by loop5/helix α2. Recently designed inhibitors additionally occupy a hydrophobic pocket of this site. The goal of the present study was to identify new fragments which fill this hydrophobic pocket and might be interesting chemical moietie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Thus, MED-SMA is an approach that may improve the efficiency and effectiveness of early stage drug discovery steps, involving the initial lead selection, improving poor leads, or, multivariate optimization, as it was used in a previous study. 17 This study demonstrates that MED-SuMo is a particularly well suited tool to both annotate protein structures and to enable structural functional classification. Finally, its effectiveness at dealing with the entire PDB shows that MED-SuMo is well-suited to large-scale applications.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Thus, MED-SMA is an approach that may improve the efficiency and effectiveness of early stage drug discovery steps, involving the initial lead selection, improving poor leads, or, multivariate optimization, as it was used in a previous study. 17 This study demonstrates that MED-SuMo is a particularly well suited tool to both annotate protein structures and to enable structural functional classification. Finally, its effectiveness at dealing with the entire PDB shows that MED-SuMo is well-suited to large-scale applications.…”
Section: Discussionmentioning
confidence: 82%
“…The full surface database which contains whole surfaces of the protein structures and the MED-Portions database also containing small protein regions but where characterized by chemical fragments detected in the ligands or peptides from the PDB. 16,17 The original version of SuMo is available on the internet, 61 but the latest improvements are only included in the MED-SuMo software distributed by MEDIT SA. 62 These improvements concern the definition and conception of protein databases and as well as the heuristic itself.…”
Section: Med-sumo Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…They applied their approach to distinct relevant target families such as GPCR and kinases. They also used this approach to study the allosteric binding site of the mitotic kinesin Eg5 [127].…”
Section: De Novo Designmentioning
confidence: 99%
“…[10] This approach was recently applied to design inhibitors of the mitotic kinesin Eg5. [11] We have previously shown that a combination of two commonly used computational approaches -pocket identification and pharmacophore screening algorithms -could be used to search the PDB for aromatic cages, i.e. sites chemically similar to known methyl-lysine binding elements, and identify novel putative sites involved in epigenetic signalling.…”
Section: Introductionmentioning
confidence: 99%